The Intentional Andragogy Model: A Teaching Framework for Counselor Educators - Phillip L. Waalkes; Paul H Smith; Daniel Hall (Teaching and Supervision in Counseling, 2023)
Counselor education programs can help support doctoral students in developing teaching philosophies. Yet, limited guidance exists about how counselor educators can help doctoral students integrate andragogies into their teaching philosophy statements. Overlooking andragogy may impede educators from deepening their philosophical beliefs and teaching with authenticity and intentionality. Therefore, we offer the Intentional Andragogy Model (IAM), a process-oriented reimagining of Halbur and Halbur’s Intentional Theory Selection model (ITSM). Counselor educators-in-training can follow this scaffolded step-by-step process to write teaching philosophy statements rooted in their life philosophies and their unique contexts. This model can help counselor educators-in-training root their teaching philosophy statements in andragogy and link andragogy and teaching practice. To illustrate this model, we present a step-by-step case example of how counselor educators can implement the IAM in a doctoral teaching course. We also present considerations for implementation of this model.
Keywords: counselor education; doctoral teaching preparation; pedagogy; andragogy; integrating theory and practice